Obraz "paradisus terrestris" w łacińskiej poezji wczesnochrześcijańskiej - Górka, Elżbieta (Vox Patrum, 2025)
The aim of this article is to analyze selected depictions of the earthly paradise in early Christian poetry, with a focus on the interweaving of biblical imagery and elements drawn from classical literature. The analysis examines passages from De ave Phoenice by Lactantius, De iudicio Domini by Pseudo-Tertullian, Cento Vergilianus de laudibus Dei by Proba, Cathemerinon by Prudentius, Alethia by Victorinus, Laudes Dei by Dracontius, and De spiritalis historiae gestis by Avitus. The poets drew not only on biblical sources – such as the imagery of Eden, the „Garden of God” from the Book of Ezekiel, and the New Jerusalem from the Book of Revelation—but also on pagan poetry, particularly the description of the Elysian Fields in Book VI of Virgil’s Aeneid and the Golden Age in Book I of Ovid’s Metamorphoses. Common characteristics of the earthly paradise include its location in the east, on a high mountain, eternal spring, the absence of dangerous weather phenomena, nature spontaneously bearing fruit, and a source from which the four rivers flow. Paradisus terrestris was portrayed as being filled with light, pleasant fragrances, and music. A frequent inhabitant of the earthly paradise was the mythical phoenix, a symbol of resurrection, which would once again open the path to paradise for humanity.